PTU-116 Increased diagnosis and treatment of HCV in prison by universal testing and use of telemedicine. (8th June 2018) - McPherson, Stuart; Hamoodi, Abi; Valappil, Manoj; Jones, Dee; Thompson, Craig; Dhuny, Julie; Robinson, Emma; Miller, Carolyn; Hewett, Margaret; Hunter, Ewan; Morey, Sarah
Abstract : Introduction: Chronic hepatitis C virus infection (HCV) is a major cause of end stage liver disease. With advances in anti-viral therapy there is an opportunity to 'eliminate' HCV from the UK. HCV is common in incarcerated individuals ( 7% of UK inmates are anti-HCV Ab positive). Increasing diagnosis and treatment of HCV in prison is a priority in order to achieve 'elimination'. However, HCV testing rates in UK prisons are low (4%). In order to increase diagnosis and treatment of HCV in the North East of England (NEE) prisons we implemented: 1. A universal offer of blood borne virus testing (UBBVT) using dry blood spot testing for prisoners at reception to increase diagnosis; 2. Prison Telemedicine clinics within NEE Prisons to increase HCV treatment rates. Aim: To review results of the implementation of UBBVT in Durham Prison (DP) and the impact of the introduction of Telemedicine HCV treatment clinics in Northumberland Prison (NP). Results: UBBVT was implemented at DP, the major remand prison in NEE, in Mar 2016. From Mar 2016 to Feb 2017 3309 BBVT offers were made in total with 2831 of the 4280 (66%) new receptions (NRs) were offered BBV testing, compared with 164 of 7, 000 NRs (2.3%) in 2013–14. 1495 (53% of offered; 35% of all NRs) NRs accepted BBV testing, of whom 95 (6.4%) were anti HCV antibody positive. Of these 47 (49.5%) were HCV RNA positive confirming active infection (3.1% of all tested). Common reasons for non-acceptance of the test were 'doesn't want it' (54%) and 'already had test' (37%). Consultant-led Telemedicine clinic (TC) with nurse in-reach was implemented in NP (a medium sentence prison) in Aug 2015. Between Aug 2015 &amp Oct 2017 80 individuals were seen in the TC. Of those seen in the TC, 57 (71%) commenced anti-HCV treatment. In 1 year prior to implementation of the TC, only 6 patients received HCV treatment. Overall, satisfaction with the TC among the prisoners was very high (80% good or excellent). Moreover, this is very cost effective with reduced cost of prisoner movement (Est £500/hospital visit). SVR and adherence data will be presented. Conclusions: A universal offer of BBV testing to prisoners at reception to prison can substantially increase testing rates and lead to many new diagnoses of HCV. Prison telemedicine clinics with nurse-led in-reach offer a cost effective and efficient method of treating HCV in the prison environment.